A Conversation with Chimeric Animal Researchers. (9th December 2022) - Craig, Kaitlynn P.
Abstract: In this conversation, three researchers from the fields of developmental biology and stem cell science—Ali Brivanlou, Lorenz Studer, and May Schwarz—speak about the importance of conducting chimeric animal experiments. The scientists describe some of the stem cell‐based chimeric research being conducted in the United States, responsibilities they have in using modified animals for experiments, and things they would like the public to understand about this research. This conversation illuminates not only what chimeric animal researchers are doing in the lab but also how their work may benefit society and where this science might go in the future .